Perkembangan Rumah Sakit Umum Daerah (RSUD) Kecamatan Mandau, Kabupaten Bengkalis (2008-2021) - Ega Karlina; Hendra Naldi (Galanggang Sejarah, 2023)
The research entitled Development of the Regional General Hospital (RSUD) in Kec. Mandau Bengkalis Regency (2008-2021) Thesis Department of History Education, Faculty of Social Sciences, Padang State University. This study raised the issue of the Development of the Regional General Hospital (RSUD) in Kec. Mandau is seen in terms of physical development and the role of the hospital. The purpose of this study was to determine the physical development and role of the Mandau District Hospital from 2008-2021. This study uses a qualitative approach to the research method, namely the historical method. The historical method consists of several stages. The first stage is heuristics or data collection. The second stage, source criticism, namely the author tests whether the data that has been found is correct or not, whether the source is really good and can be trusted. The third stage, interpretation. The fourth stage, historiography, in which the writer writes the data obtained into a scientific work. The results of this study found that the Mandau District General Hospital began functioning in 2008, related to hospital facilities or infrastructure that continued to make improvements in each period.